KAJIAN KEAMANAN PEMAKAIAN OBAT ANTI-HIPERTENSI DI POLIKLINIK USIA LANJUT RS DR. SARDJITO - Ikawati, Zullies; Djumiani, Sri; P.S, I Dewa Putu (Indonesian Research Gateway)
Hypertension is one of diseases that its prevalence increases along with increasing age. This study aimed to identify and study the safety of anti-hypertension drug use at the elderly polyclinic of Dr. Sardjito Hospital Outpatient Installation by identifying and evaluating contraindication, interaction and side effect of anti-hypertension drugs. This was a descriptive study with data taken prospectivelly from 80 patients from November 14 to December 13, 2005. Data were obtained from medical records, interviews and questionnaires. The study on contraindication, interaction and side effect of drugs which happened was based on a guideline book. There was 27.5% of patients took antihypertension drugs which were not beneficial to patients' clinical condition, as much as 41.3% of patients took combined drugs potential to cause interaction, 8.7% of which had clinical symptoms presumed to be related with possibility of increasing drug interaction effect. As much as 33.8% of patients had at least one drug side effect considered to be related or possibly related with anti-hypertension medication. It was concluded that the use of anti-hypertension drugs among the elderly at Dr. Sardjito Hospital Outpatient Installation had not been relatively safe so that monitoring of anti-hypertension drugs use was needed. ABSTRAK Penelitian ini bertujuan untuk mengetahui dan mengkaji keamanan pemakaian obat anti-hipertensi di Poliklinik usia lanjut Instalasi rawat jalan RS Dr. Sardjito Yogyakarta, dengan mengkaji kontraindikasi, interaksi dan efek samping obat anti-hipertensi yang digunakan. Penelitian ini merupakan penelitian deskriptif dengan pengambilan data secara prospektif dari 80 pasien poliklinik usia lanjut instalasi rawat jalan RS Dr. Sardjito periode 14 November - 13 Desember 2005. Data diambil dari rekam medik, wawancara dan mengajukan kuesioner kepada pasien. Kemudian mengkaji kontraindikasi, interaksi dan efek samping obat yang terjadi berdasarkan buku pedoman. Hasil penelitian menunjukkan terdapat 27,5 % pasien menerima obat anti-hipertensi yang tidak menguntungkan terhadap kondisi klinis pasien, sehingga pemakaiannya diperlukan pengawasan. Terdapat 41,3 % pasien menerima kombinasi obat yang potensi terjadi interaksi, 8,7 % diantaranya mempunyai gejala klinis yang diperkirakan berkaitan dengan kemungkinan berkembangnya efek interaksi obat. Sebanyak 33,8 % pasien mengalami sedikitnya satu efek samping obat yang dipertimbangkan berkaitan atau kemungkinan berkaitan dengan pengobatan antihipertensi.